The Effect of Fintech Implementation on The Performance of SMEs - Novia Utami; Marsiana Luciana Sitanggang (Journal of International Conference Proceedings, 2021)
The emergence of FinTech has now made the unstoppable growth of technology in this digital era complete. Defined as technology-based financial services, FinTech allows transactions to be processed anywhere and anytime. It has provided small and medium enterprises (SMEs) with advantages, from provision of capital funding to ease of transactions that supports growth in SMEs. This study aims to identify how FinTech adoption and financial literacy affect Indonesian SMEs’ performance. Online questionnaires were distributed among respondents—100 business owners—selected using convenience sampling technique, and data were then analyzed using OLS regression. It was later found that FinTech adoption positively and significantly influences SMEs’ performance. Financial literacy, at the same time, strengthen the association between FinTech adoption and SMEs’ performance.